2152. Types and Resistance Patterns of Gram-negative Bacteria (GNB) causing Bloodstream Infections (BSIs) in a Neonatal ICU (NICU), 2010-2019. (15th December 2022) - Frantzis, Irene; Paul, Anshu; Gentzler, Eliza; Solowey, Kyra; Manickam, Surya; Hill-Ricciuti, Alexandra; Messina, Maria; Alba, Luis; Johnson, Candace L; Brachio, Sandhya S; Saiman, Lisa
Abstract: Background: BSIs caused by GNB, particularly with multidrug resistance, cause substantial morbidity and mortality in NICUs worldwide 1 . We previously reported low overall rates of gentamicin resistance in commonly isolated GNB, i.e., Escherichia coli and Klebsiella species, supporting gentamicin as empiric therapy in our NICU 2 . Over a decade later, we sought to assess GNB BSI rates and potential changes in GNB resistance patterns. References: < ! 1.Dramowski A, et al. Paediatr Int Child Health. 2015;35:265-72. 2.Smith A, et al. Pediatr Infect Dis J 2010;29:831–35. Methods: We retrospectively reviewed GNB BSIs that occurred in infants > 3 days old admitted to a level IV academically affiliated NICU from 2010-2019. Pre-approval for broad spectrum antibiotics was in place throughout the study period. Post-prescription review began in 2017. We collected the types of GNB and resistance to gentamicin, 3 rd /4 th generation cephalosporin agents, and meropenem. Data analysis included frequency of GNB type per year, incidence per 1000 admissions, and regression analysis Results: Admissions were generally stable during the study period (range 855-1057). The types of GNB causing BSIs each year and BSI incidence are shown (Figure 1). Incidence ranged from 8-26 per 1000 admissions and during the 10-year period, GNB BSI incidence decreased (p< 0.001). The most common GNB were E. coli (n=21) and Klebsiella spp. (n=25) followed by Enterobacter spp. (n=15) and Serratia marcescens (n=12). GNB resistance trends are shown (Figure 2). Overall, resistance to gentamicin appeared stable (14.5%), while resistance to ceftriaxone increased (19.1%) and resistance to cefepime (3.8%) and meropenem (2.3%) was rare. Conclusion: GNB BSIs have decreased in our NICU with low rates of gentamicin resistance, supporting the continued use of gentamicin for empiric antibiotic therapy. To maintain low resistance rates, antimicrobial stewardship efforts should continue. NICU-specific antibiograms should be considered to facilitate assessment of resistance trends. Funding: IF supported by NIAID T32 AI007531. Disclosures: Lisa Saiman, MD MPH, Merck & Co., Inc.: Advisor/Consultant|Merck & Co., Inc.: Grant/Research Support.